Leiomyosarcoma with partial rhabdomyoblastic differentiation - Mohammad, Zulkarnaen; Dayangku Norlida, Awang Ojep; Than, Than Aye; Chan, Wai Hoong (2022)
Leiomyosarcoma (LMS) is a malignant neoplasm showing pure smooth muscle differentiation. LMS with rhabdomyoblastic component in the soft tissue is a rare entity described in only few cases in the literature. Previous studies of LMS with rhabdomyoblastic differentiation have indicated a poorer prognosis of this tumour compared to the classical LMS. Case Report: A 78-year-old male patient presented with a painful mass at the right scapula for 4 years. Excision was performed and histopathological diagnosis was LMS grade 2 with involvement of the surgical margins. Subsequent serial radiological scans revealed no disease progression. However, he developed recurrence one year after the initial excision. A second wide local excision was performed with right total scapulectomy. The tumour showed hypercellularity with a mixture of caldesmon and desmin positive spindled cells arranged in fascicles and desmin positive large multinucleated cells with abundant cytoplasm (rhabdomyoblastic cells). Areas of positivity towards myogenin were also seen. Thus, a diagnosis of recurrent LMS with partial rhabdomyoblastic changes was rendered. Discussion: Leiomyosarcoma of the soft tissue account for 5 to 10% of soft tissue sarcoma. The presence of rhabdomyoblastic cells has been reported in various types of malignancy and has been determined to be a predictor of aggressive behaviour of neoplasms regardless of tumour histogenesis. The coexistence of rhabdomyoblastic component within LMS represent a poorer prognostic parameter.